Comparative study of electrochemical properties of SnS and SnS2 as anode materials in lithium-ion batteries. (10th February 2023) - Glibo, Albina; Eshraghi, Nicolas; Surace, Yuri; Mautner, Andreas; Flandorfer, Hans; Cupid, Damian M.
Highlights: After 100 cycles, SnS2 exhibits a capacity of 369 mAhg −1 whereas that of SnS is only 133 mAhg −1 . SnS electrodes exhibit higher volume expansions than SnS2 electrodes. The volume expansion of tin-sulfide electrodes partially depends on the amount of Li2 S. In the conversion reaction, SnS2 yields double the amount of Li2 S, thereby exhibiting lower volume expansions. Abstract: Phase pure SnS and SnS2 were synthesized via the precipitation reaction and investigated as active anode materials for lithium-ion batteries. The crystal structure, morphology and chemical composition of the as-synthesized materials were determined by various physio-chemical techniques such as powder X-ray diffraction, scanning electron microscopy, transmission electron microscopy and X-ray photoelectron spectroscopy. The electrochemical properties of the SnS and SnS2 active anode materials were investigated by galvanostatic cycling with potential limitation, cyclic voltammetry, electrochemical impedance spectroscopy and electrochemical in-situ dilatometry. It was shown that the SnS2 electrodes exhibit superior cycling performance properties compared to the SnS electrodes. This is due to the higher amount of Li2 S which is produced during the conversion reaction of SnS2 as well as to the intercalation of Li into the SnS2 crystal structure prior to conversion, which allows for a finer distribution of Li2 S within the electroactive material. Graphical abstract: Image, graphical abstract